Fungal bioaerosol as an occupational hazard in the podiatrist's workplace. Issue 2 (1st February 2023) - Alija-Martínez, Beatriz; Becerro de Bengoa Vallejo, Ricardo; Sevillano Fernández, David; González, Natalia; Losa Iglesias, Marta Elena; Collado, Luis; Espinosa-Rubio, Rubén; Alou, Luis
ABSTRACT: Previous studies have reported the potential emission of nail dust to the indoor air of the podiatrist's workplace during nail drilling procedures. The main objective of this study was to analyse the fungal bioaerosol present in the indoor air of podiatry rooms, including during the nail drilling procedure. Seventeen private clinics were sampled in Madrid during spring and summer. The most prevalent filamentous fungi detected were Cladosporium spp. and Penicillium spp. in both seasons. The presence of Trichophyton rubrum and Trichophyton interdigitale was reported in samples during the drilling procedures, establishing a positive association with the clinical suspicion of onychomycosis (p = 0.002) and the utilization of aspiration systems (p=0.04). The present study concludes that airborne fungal concentrations in podiatrist's clinics are consistent with national and international guidance. Occupational exposure to dermatophytes may briefly occur during definite periods across the daily activity despite the use of dust aspiration systems.